2013
DOI: 10.2298/hemind120327047p
|View full text |Cite
|
Sign up to set email alerts
|

Sensory and color properties of dietary cookies with different fiber sources during 180 days of storage

Abstract: The aim of this study was to examine the sensory properties of dietary cookies produced with addition of different dietary fiber sources (inulin and ligofructose, oat flakes, mixture of oat flakes and wholemeal flour, wholemeal flour and mixture of wholemeal flour and carob flour), and to measure instrumentally color changes of cookies upper and lower surfaces, after storage at temperatures of 18-20°C for 180 days. Addition of inulin and oligfructose was determined to be the fiber source with the highest impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 33 publications
(38 reference statements)
0
16
0
1
Order By: Relevance
“…Dietary fibers either as component of different flour or in their pure forms that is, inulin, were also reported by Popov‐Raljic et al . () to be associated with loss in cookies textural properties during storage. Cookies supplemented with PoPx were found very much compatible to the control samples during entire storage period and were liked very much to moderate with increasing rate of supplementation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary fibers either as component of different flour or in their pure forms that is, inulin, were also reported by Popov‐Raljic et al . () to be associated with loss in cookies textural properties during storage. Cookies supplemented with PoPx were found very much compatible to the control samples during entire storage period and were liked very much to moderate with increasing rate of supplementation.…”
Section: Resultsmentioning
confidence: 99%
“…Reduction in acceptability score for both of the mentioned attributes might be associated to the improved fiber pool of cookies added vide Pbg supplementation and its better ability to bind moisture. Dietary fibers either as component of different flour or in their pure forms that is, inulin, were also reported by Popov-Raljic et al (2013) to be associated with loss in cookies textural properties during storage. Cookies supplemented with PoPx were found very much compatible to the control samples during entire storage period and were liked very much to moderate with increasing rate of supplementation.…”
Section: Organoleptic Acceptability Of Pbg and Popx Supplemented Cookiesmentioning
confidence: 97%
“…According to ΔE value, color differences were categorized as: imperceptible (0-0.5), slightly noticeable (0.5-1.5), noticeable (1.5-3.0), significantly noticeable (3.0-6.0), extremely noticeable (6.0-12.0) and colors of different shades (above 12.0) (Popov-Raljić et al 2013).…”
Section: Color Parametersmentioning
confidence: 99%
“…For this project, the panelists received further orientation on dried dog food using samples that may or may not be included in the study. Panels of similar size and training have been reported in other recent research [8,9,10]. …”
Section: Methodsmentioning
confidence: 61%
“…Other studies on bread showed that a higher content of dietary fibers resulted in smaller cells in the crumb, which in turn resulted in a more dense appearance [7]. Popov-Ralić et al [8] observed that different fiber content in cookies mostly impacted the appearance of the products, in particular the color.…”
Section: Introductionmentioning
confidence: 99%